RETRACTED: Resveratrol Preincubation Enhances the Therapeutic Efficacy of hUC-MSCs by Improving Cell Migration and Modulating Neuroinflammation Mediated by MAPK Signaling in a Mouse Model of Alzheimer’s Disease - Wang, Xinxin; Wu, Junwei; Ma, Shanshan; Xie, Ya; Liu, Hongtao; Yao, Minghao; Zhang, Yanting; Yang, Greta Luyuan; Yang, Bo; Guo, Ruixia; Guan, Fangxia (Frontiers in Cellular Neuroscience, 2020)
Human umbilical cord-derived mesenchymal stem cells (hUC-MSCs) are promising for the treatment of Alzheimer’s disease (AD). However, their low rate of migration and survival in the brain limit their clinical applicability. This study is designed to improve the therapeutic potential of hUC-MSCs by preincubating them with resveratrol, a natural polyphenol capable of regulating cell destiny. Herein, we demonstrate that resveratrol preincubation enhances the migration of hUC-MSCs in vitro, as well as their survival and homing into the hippocampus of AD mice in vivo. Moreover, resveratrol-primed MSCs were better able to inhibit amyloid-β peptide (Aβ) deposition, Tau hyperphosphorylation, and oxidative stress, all the while improving learning and memory. Notably, we found that hUC-MSCs inhibited neuroinflammation by reacting with astrocytes and microglial cells and suppressing mitogen-activated protein kinases (MAPKs), extracellular signal kinases (ERK), p38 kinases (p38), and c-Jun N-terminal kinases (JNK) signaling pathways in the hippocampus of AD mice. Furthermore, resveratrol pretreatment enhanced these effects. Conclusively, the current study revealed that resveratrol preconditioning protected hUC-MSCs against the hostile microenvironment characteristic of AD, and enhanced their viability and homing into the brain of AD mice. Resveratrol-pretreated hUC-MSCs is thereby proposed to be a promising therapy for AD.